Case Series of Wounded Warriors Receiving Initial Fit PowerKnee™ Prosthesis. Issue 2 (April 2017) - Pasquina, Paul F.; Carvalho, Antonio J.; Murphy, Ian; Johnson, Jessica L.; Swanson, Thomas M.; Hendershot, Brad D.; Corcoran, Michael; Ritland, Bradley; Miller, Matthew E.; Isaacson, Brad M.
ABSTRACT: Introduction: Combat-related lower-limb amputations challenge prosthetic device prescription and rehabilitation practices. Moreover, wounded warriors are relatively young and lived highly active lifestyles before injury, underscoring their eagerness to quickly regain independent mobility and higher levels of physical function. Methods: Four US military service members with combat-related unilateral amputation were fit with the PowerKnee™ as their initial prosthesis. Results: All patients achieved significant mobility milestones more rapidly than historical norms of similarly injured patients using other prosthetic knees. Level-ground gait analysis of each patient was comparable with historical normative data of patients using advanced microprocessor variable dampening knee (MPK) prostheses, although the PowerKnee users generated less power in their intact limb hip and knee, suggesting less strain on intact joints. Each patient was also subsequently fit with an MPK and offered a hydraulic knee prosthesis for higher-level activities. Two of the four patients ultimately chose an alternative prosthesis as their primary knee, citing weight, ability to run, and battery life as key determinants. All patients, however, perceived the PowerKnee prosthesis to be valuable during their rehabilitation. Conclusion: The PowerKnee may be a viable option for the initial prosthetic fitting of individuals with transfemoral amputation. Further research is necessary to better understand the advantages or disadvantages of powered prosthetic technology, including their biomechanical effects on intact limbs, especially for high-level activities, and their ability to enhance early rehabilitation and optimal patient selection and timing of fitting.